Inquadramento del paziente fragile: dalla scienza di base alla clinica - Tarantino, U.; Feola, M.; Scimeca, M. (Lo Scalpello - Journal, 2018)
MANAGEMENT OF THE FRAIL PATIENT: FROM BENCH TO BEDSIDE The ageing of the population leads to an increase in the incidence of chronic-degenerative diseases such as osteoporosis. It causes macro- and microarchitectural alterations with a consequent risk of falling and fracture. The progressive subversion of the muscular structure typical of osteoporosis-related sarcopoenia contributes to the “frailty syndrome” that often affects elderly patients.